SYAIKH ABUL FADHOL SENORI AND HIS CONTRIBUTION TO THE DISSEMINATION OF HADITH IN INDONESIA - Yahya, Yuniar Indra (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2023)
The findings of the manuscripts of sanad KH. Abul Fadhol Senori Tuban sourced from KH. Hasyim Asy'ari added to the treasures of hadith science in Indonesia. This research reveals; process of al-Taḥammul wa al-Adā' Abul Fadhol Senori, the role and contribution of Abul Fadhol Senori in spreading hadith, and level of his expertise in hadith. For this reason, the author interviewed several families of Abul Fadhol, analyzed the manuscripts found, and examined his books. This study found that the process of al-Taḥammul Abul Fadhol is by way of a Ijazah Mua'yyan li Mu'ayyan. As well as the al-Adā' process is a of Ijazah Mua'yyan li Mu'ayyan and Munāwalah Maqrūnah bi al-Ijāzah. As for his contribution in the spread of hadith namely; 1) Holding a hadith assembly, 2) Codifying the sanad of KH. M. Hasyim Asy'ari, 3) Ijazah his hadith books, 4) Doing Fiqh al-Hadith. So it can be concluded that Abul Fadhol Senori is an Al-Musnid and Al-Faqīh. [Misykāt Temuan manuskrip sanad KH. Abul Fadhol Senori Tuban yang bersumber dari KH. Hasyim Asy’ari menambah khazanah dalam ilmu hadis di Indonesia. Penelitian ini mengungkap; proses al- Taḥammul wa al-Adā' Abul Fadhol Senori, peran dan kontribusi Abul Fadhol Senori dalam menyebarkan hadis, serta level keahlian beliau di bidang hadis. Untuk itu, penulis mewawancarai beberapa keluarga Abul Fadhol, menganalisis manuskrip yang ditemukan, serta menelaah karya-karyanya. Penelitian ini menemukan bahwa proses tahammul Abul Fadhol adalah dengan cara Ijazah Mua’yyan li Mu’ayyan. Sedangkan adā’-nya adalah ijazah mu’yyan li mu’yyan dan munawalah maqrūnah bi al-ijazah. Adapun kontribusi beliau dalam penyebaran hadis, yakni; 1) Menggelar majelis hadis, 2) Mengkodifīkasi sanad dari KH. M. Hasyim Asy’ari, 3) Mengijazahkan kitab-kitab hadis, 4) menulis Fīqh al-Ḥadīṣ. Sehingga dapat disimpulkan bahwa Abul Fadhol Senori merupakan seorang Al-Musnid dan Al-Faqīh.]